St. John's Wort Has Metabolically Favorable Effects on Adipocytes In Vivo. (20th May 2014) - Fuller, Scott; Richard, Allison J.; Ribnicky, David M.; Beyl, Robbie; Mynatt, Randall; Stephens, Jacqueline M.
Abstract : In addition to serving as a storage site for reserve energy, adipocytes play a critical role in whole-body insulin sensitivity and glucose metabolism. St. John's Wort (SJW) is a botanical supplement widely used as an over-the-counter treatment of depression and a variety of other conditions associated with anxiety and nerve pain. Previous studies in our laboratory demonstrated that SJW inhibits insulin-stimulated glucose uptake and adipocyte differentiation in cultured murine and mature human adipocytes. To investigate the effects of SJW on adipocyte function in vivo, we utilized C57BL/6J mice. In our studies, mice were administered SJW extract (200 mg/kg) once daily by gavage for two weeks. In contrast to our in vitro studies, mice treated with SJW extract showed increased levels of adiponectin in white adipose tissue in a depot specific manner ( P < 0.01 ) . SJW also exerted an insulin-sensitizing effect as indicated by a significant increase in insulin-stimulated Akt serine phosphorylation in epididymal white adipose tissue ( P < 0.01 ) . Food intake, body weight, fasting blood glucose, and fasting insulin did not differ between the two groups. These results are important as they indicate that SJW does not promote metabolic dysfunction in adipose tissue in vivo .